Analisis Tingkat Kesehatan Bank Dinilai Menggunakan Rasio CAMEL dan Rasio RGEC pada PT. BRI Srikaton) - Subianto; Miki Indika; Muhammad Rezeki (Jurnal Kajian Akuntansi dan Auditing, 2021)
The aim of this study is to see the health level of BRI (Bank Rakyat Indonesia) of 2018 and 2019 by CAMEL and RGEC ratio. This study is quantitative study. Collection data technique of this study are interview and documentation while analyzing data technique is through descriptive method where CAMEL is consisted of capital, asset quality, management quality, feasibility and liquidity factor while RGEC is consisted of risk profile, good corporate governance, and earning factor. Based on the result of this study, CAMEL of 2018 and 2019 are 99,41 and 99,23 categorized as “health”. RGEC of 2018 and 2019 are 96,67 percent categorized as “health”. Keywords: Health level, CAMEL, RGEC